Method and Evaluation of Habitability in Emergency Temporary Housing in Lower-income Countries: Five Case Studies in Peru - Acevedo De los Ríos, Alejandra (2024)
In lower-income countries, the risk of disasters is constant due to the high physical vulnerability of housing, primarily due to informal construction practices and a lack of government planning and control. Emergency Temporary Housing (ETH) is a crucial relief for families in need after a disaster, providing shelter and support. However, these temporary structures often fall short when considering the affected communities' broader social and environmental aspects. Issues such as inadequate design, insufficient attention to local customs, and environmental impact are common, compromising the long-term well-being and resilience of the affected population. This research analyzes habitability conditions in ETH through five case studies in Peru's three macro-regions: the coastal, highland, and jungle regions. The methodology involves a literature review and the identification of specific minimum standards for habitability variables based on international manuals and the design of a matrix for data analysis to evaluate the cases across three spheres (housing, camp, and city) and three main dimensions (physical-spatial, physical-environmental, and psychosocial). The fieldwork included environmental monitoring equipment, thermal comfort surveys, social surveys, well-being surveys, and in-depth key interviews. Variables such as health, privacy, and security scored poorly on the housing scale, while economy and life span variables obtained higher scores. At the camp scale, participation, community organization, and size variables scored 33%, contrasting with the social cohesion variable averaging 57%. The city scale indicated a critical state of the governance, highlighting the disconnection between the different stakeholders. The study's findings on habitability conditions in Peru's ETH are pivotal for refining local design guidelines and procurement terms and offer a universally applicable framework. By applying these insights in lower-income countries, stakeholders can significantly enhance living conditions in ETH, extending the benefits of this research far beyond Peru and aiding in improving ETH standards worldwide. © 2024 Institute of Physics Publishing. All rights reserved.